Environmental context and differences between native and invasive observed niches of Batrachochytrium salamandrivorans affect invasion risk assessments in the Western Palaearctic. Issue 12 (4th July 2018) - Beukema, Wouter; Martel, An; Nguyen, Tao Thien; Goka, Koichi; Schmeller, Dirk S.; Yuan, Zhiyong; Laking, Alexandra E.; Nguyen, Truong Quang; Lin, Chun‐Fu; Shelton, Jennifer; Loyau, Adeline; Pasmans, Frank
Abstract: Aim: Identifying hosts and regions susceptible to invasion by an emerged pathogen is vital to inform early risk assessments. We here show how differences between a pathogen's native and invasive observed niche and their underlying environments affect this process, using the recent emergence of Batrachochytrium salamandrivorans ( Bsal ) as a critical, empirical example. Location: Palaearctic. Methods: To quantify observed niches, we first gathered occurrences from the native Asian and invasive European distribution of Bsal . Through ordination in PCA‐bound environmental space, we then applied overlap tests to compare native and invasive Bsal niches with those of 56 putative Western Palaearctic host species. At last, we ensembled bivariate niche models (ESMs) for each Bsal niche to assess how differences in observed niches influenced suitability predictions. Results: The observed invasive Bsal niche is a conservative, partially filled subset of its wider native niche. Pathogen–host overlap measured using the narrow invasive niche was nevertheless found to be significantly higher than that of the native niche, which is partly situated in subtropical conditions absent from the Western Palaearctic. ESMs created using the native niche predict high suitability for Bsal throughout Europe. Conversely, a more restricted range was predicted using the invasive niche, which coincides with the presence of oceanic climates in north‐western Europe and several Mediterranean mountain ranges. Main conclusions: Unequal relative availability of environments in native and invasive ranges may lead to underestimation of observed niche overlap between native pathogen populations and putative hosts in the invasive range. The existence of partially filled niches may add uncertainty to overlap measurements, and predictions of potential further spread. Results based on the invasive niche therefore provide a conservative estimate; yet demonstrate, in our case, that Bsal is already present in conditions shared by numerous host species. Further niche filling may accordingly increase risk of salamander diversity across the Western Palaearctic.